Is gallbladder PoCUS diagnostic accuracy accessible to medical students after PoCUS training exclusively on healthy volunteers? A pilot randomized control trial - Florence Dupriez; Bastian Rodrigues de Castro; Félix Gendebien; Antoine Fasseaux; Matthieu Gensburger; Laurent Marissiaux; Andrea Penaloza; Xavier Bobbia; Robert Jarman (The Ultrasound Journal, 2023)
Abstract Background Point-of-care ultrasound (PoCUS) is increasingly used in clinical practice and is now included in many undergraduate curricula. Here, we aimed to determine whether medical students who participated in a PoCUS teaching program with several practical training sessions involving healthy volunteers could achieve a good level of diagnostic accuracy in identifying gallbladder pathologies. The intervention group (IG) was trained exclusively on volunteers with a healthy gallbladder, whereas the control group (CG) had access to volunteers with a pathological gallbladder as recommended in most PoCUS curricula. Materials and methods Twenty medical students were randomly assigned to the IG and CG. After completing the training program over 2 months, students were evaluated by three independent examiners. Students and examiners were blind to group allocation and study outcome. Sensitivity and specificity of students’ PoCUS gallstone diagnosis were assessed. Secondary outcomes were students’ confidence, image quality, acquisition time, and PoCUS skills. Results Sensitivity and specificity for gallstone diagnosis were, respectively, 0.85 and 0.97 in the IG and 0.80 and 0.83 in the CG. Areas under the curve (AUC) based on the receiver operating characteristic curve analysis were 0.91 and 0.82 in the IG and CG, respectively, with no significant difference (p = 0.271) and an AUC difference of -0.092. No significant between-group difference was found for the secondary outcomes. Conclusions Our pilot study showed that medical students can develop PoCUS diagnostic accuracy after training on healthy volunteers. If these findings are confirmed in a larger sample, this could favor the delivery of large practical teaching sessions without the need to include patients with pathology, thus facilitating PoCUS training for students.